Associative learning in patients with cerebellar ataxia. - Tucker, J; Harding, A; Jahanshahi, M; Nixon, P; Rushworth, M; Quinn, N; Thompson, P; Passingham, R (1996)
It has been claimed that patients with cerebellar pathology are impaired at associative learning. Patients with cerebellar ataxia (n = 7) were taught a visual-motor associative task. The task was chosen so as to allow comparisons with data currently being collected on the effects of cerebellar lesions on associative learning in monkeys. As a group the patients were as impaired at learning the task as a group of 8 patients with Huntington's disease. When each patient was individually matched with a control of the same age and IQ, some patients with cerebellar ataxia were found to be clearly impaired, but 2 were not. Of the 4 patients who were most clearly impaired, 2 had brainstem pathology and 2 did not. The relevance of these findings is discussed in relation to views concerning the functions of the cerebellum.